2000
DOI: 10.1046/j.1365-2125.2000.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altered gastric emptying and gastrointestinal motility on metformin absorption

Abstract: Aims The purpose of this in vivo human study was to assess the effect of altered gastric emptying and gastrointestinal motility on the absorption of metformin in healthy subjects. Methods An open-label, three treatment, three period crossover study was conducted in 11 healthy volunteers. Each subject received 550 mg metformin hydrochloride in solution alone; 5 min after a 10 mg i.v. dose of metoclopramide; and 30 min after a 30 mg oral dose of propantheline. Metformin solution was radiolabeled by the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 13 publications
5
62
0
Order By: Relevance
“…Previously, Marathe et al showed that the systemic availability of metformin, which is primarily absorbed in the small intestine, is significantly improved with delayed GE (Marathe et al, 2000). Oberle and Amidon linked the double peak phenomenon in plasma levels of cimetidine with the variable gastric emptying and transit along the intestinal tract combined with a short plasma elimination half-life and poor absorption (Oberle and Amidon, 1987).…”
Section: Invasive Methodsologiesmentioning
confidence: 99%
“…Previously, Marathe et al showed that the systemic availability of metformin, which is primarily absorbed in the small intestine, is significantly improved with delayed GE (Marathe et al, 2000). Oberle and Amidon linked the double peak phenomenon in plasma levels of cimetidine with the variable gastric emptying and transit along the intestinal tract combined with a short plasma elimination half-life and poor absorption (Oberle and Amidon, 1987).…”
Section: Invasive Methodsologiesmentioning
confidence: 99%
“…The absence of monomers was ensured spectrometrically by ensuring that the water of the washings did not contain any trace of monomers. The SPH was dried in an oven at 60°C for 6 hours [5][6][7][8].…”
Section: Synthesis Of Superporous Hydrogel Compositementioning
confidence: 99%
“…Moreover, lactic acidosis, which is sometimes fatal, has occurred with biguanides (Sweetman, 2007). Development of novel formulation strategies for metformin might be useful to improve its bioavailability, to reduce the dosing frequency and to decrease gastrointestinal side effects and toxicity (Marathe et al, 2000;Cetin et al, 2013;Basavaraj & Betageri, 2014). Also, these systems may be helpful for effective use of metformin in cancer treatment (Alexis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%